Intrapreneur Intention in Surabaya, Indonesia: as the Impacts of Entrepreneurial Orientation - Christina Yanita Setyawati; Helena Sidharta; Eko Setya Dharma (Institute of Computer Science (IOCS), 2022)
In general, Indonesian people are more interested in becoming employees than entrepreneurs. Based on Google’s search engine, the popularity of employee as an occupation is shown at 81 in a scale of 1-100. There is increasing demand for employees who are able to perform many functions at work. As an educational institution with a focus on entrepreneurship, Ciputra University established a Corporate Entrepreneurship (CE) guild. The increasing number of guild members indicates higher intrapreneurial intention, which is influenced by entrepreneurial orientation. Therefore, the purpose of this research is to determine the role of entrepreneurial orientation dimensions, which are Innovativeness, Need for Achievement, Networking, Proactiveness, and Risk Taking, on the intrapreneurial intention of Corporate Entrepreneurship students in Ciputra University. This research is a quantitative research with Multiple Linear Regression as analysis technique. The population of this study is the first and second generations of Corporate Entrepreneurship students with a sample of 118 respondents. Furthermore, questionnaire is used as a means to obtain research data. The outcome of this research indicates that Innovativeness, Need for Achievement, and Networking have significant effects on intrapreneurial intention. On the other hand, Proactiveness and Risk Taking have no significant effects on intrapreneurial intention.